2011
DOI: 10.1111/j.1476-5829.2011.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum neopterin, sialic acid and nitric oxide levels in dogs with malignant mammary tumours

Abstract: Mammary cancer is one of the leading causes of death in pet population. Early diagnosis and malignancy detection is important for prognosis. The levels of neopterin, sialic acid and nitric oxide in serum of dogs with malignant mammary tumours were evaluated to investigate the importance of these biochemical parameters for malign mammary tumour. Twelve healthy dogs and twenty dogs with malignant mammary tumours were used as research materials. Blood samples were collected from both groups for neopterin analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Our findings are consistent with the results of the studies performed by Askar et al (2009) and Tascene et al (2011), who demonstrated a significantly higher level of NO in the serum of female dogs with malignant mammary gland tumours as compared to healthy dogs.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with the results of the studies performed by Askar et al (2009) and Tascene et al (2011), who demonstrated a significantly higher level of NO in the serum of female dogs with malignant mammary gland tumours as compared to healthy dogs.…”
Section: Discussionsupporting
confidence: 83%
“…According to the studies performed recently by Tascene et al . there were no significant differences between serum neopterin levels in female dogs with malignant mammary tumours and healthy animals . This study involved only 20 female dogs with malignant mammary tumours (classified according to Moulton (1990) histopathological classification of canine mammary tumours), and were mainly tubular malignant mixed tumours.…”
Section: Discussionmentioning
confidence: 54%
“…The data regarding neopterin concentration in female dogs with mammary tumours are scarce. According to the studies performed recently by Tascene et al . there were no significant differences between serum neopterin levels in female dogs with malignant mammary tumours and healthy animals .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some authors have suggested that urinary NEO is only produced in detectable forms and concentrations in humans and nonhuman primates 31 44 , a number of studies of stress and immune responses in other mammals have included measurements of serum NEO, suggesting the potential for much broader applicability (e.g. dogs 45 ; pigs 46 ; cattle, horses, lamas, dogs, cats and rats 47 ).…”
Section: Discussionmentioning
confidence: 99%